Relationship Between Geomagnetic Storms and Auroral/Magnetospheric Substorms: Early Studies - Akasofu, Syun-Ichi (Frontiers in Astronomy and Space Sciences, 2020)
This paper describes a short story of how I learned that there is the direct relationship between geomagnetic storms and auroral/magnetospheric substorms in the 1960s and 1970s; in those days, both geomagnetic storms and auroral substorms were almost independent subjects. It is now understood that auroral substorms are directly related to the development of the ring current and thus of the main phase of geomagnetic storms. Further, we have begun to recognize that the growth of the ring current (caused by auroral/magnetospheric substorms) will change the internal structure of the magnetosphere, which in turn will change and could modify at least the intensity of auroral substorms. Thus, there is an interesting feed-back processes between them. It is expected that this feed-back relationship between geomagnetic storms and auroral/magnetospheric substorms will become one of the major issues in magnetospheric physics in the future. In fact, an effort to understand this relationship will deepen our understanding of both geomagnetic storms and auroral/magnetospheric substorms.